Percutaneous Route of Life: Chylothorax or Total Parenteral Nutrition-Related Bilateral Pleural Effusion in a Neonate?. (6th October 2021) - Alhatem, Albert; Estrella, Ydamis; Jones, Anja; Algarrahi, Khalid; Fofah, Onajovwe; Heller, Debra S.
Abstract: Objective: Peripherally Inserted Central Catheter (PICC) lines are an essential tool in the management of premature neonates. Pleural effusion (PLE) secondary to the leakage of alimentation into the pleural cavity is an encountered complication of central-line total parenteral nutrition (TPN) administration. Methods: We review a case of a premature neonate who suffered large, bilateral PLE after insertion of an upper extremity PICC line for TPN. Results: Pleural fluid biochemical analysis confirmed PICC line infiltration, predominantly with monocytes, low protein, high triglycerides and high glucose. These results favored TPN leakage over chylothorax. Conclusions: To our knowledge, this is the first case of bilateral PLE due to PICC complication in a neonate, which highlights the importance of chylothorax differential diagnosis, the role of autopsy, and the need for clinical precautions when providing premature neonates with high osmolarity TPN.